Microbial pesticides: a bibliometric analysis of global research trends (1973–2024) - Weerachon Sawangproh; Paiphan Paejaroen; Lutfi Afifah; Chetsada Phaenark (Egyptian Journal of Biological Pest Control)
Abstract Background Microbial pesticides, derived from microorganisms such as bacteria, fungi, and viruses, present sustainable alternatives to chemical pesticides, thereby promoting environmentally friendly agricultural practices. This bibliometric analysis examines the evolution of microbial pesticide research from 1973 to October 2024, utilizing the Scopus database to identify trends, geographic distribution, collaboration networks, and key research areas. Results A total of 247 articles were analyzed, revealing an annual growth rate of 5.16%, with a significant increase in publications over recent decades. This upward trend indicates a shift towards ecologically conscious pest management. China leads in research output with 341 publications, followed by USA (227) and India (126), highlighting strong international collaboration, particularly between China and USA, where many publications are co-authored by researchers from multiple countries. The primary research areas include Agricultural and Biological Sciences, alongside substantial contributions from Environmental Science and Immunology. The analysis identified thematic clusters, emphasizing key microbial agents such as Bacillus thuringiensis for pest control agent. Key journals, including Biocontrol Science and Technology, Journal of Biopesticides, and Journal of Invertebrate Pathology, serve as essential platforms for disseminating these findings. Conclusion The findings reflect an increasing recognition of microbial pesticides in integrated pest management, aligning with global trends toward sustainable agricultural practices and food safety by reducing reliance on chemical pesticides. Contributions from institutions such as Fujian Agriculture and Forestry University and Guizhou University in China further highlight the academic support driving advancements in this field.